Pembentukan karakter religius mahasiswa melalui kegiatan tahfidz Al-Qur’an di Pondok Pesantren Nurul Furqon 2 Lowokwaru Malang - Astuti, Siti Zuni (Maliki Interdisciplinary Journal, 2023)
Tahfidz Islamic Boarding School for Students Nurul Furqon 2 Malang is an Islamic boarding school that is here to provide solutions for students and female students who live in the city of Malang. Activities at the Nurul Furqon 2 Malang Islamic Boarding School can divide the time for mandatory Islamic boarding school activities without neglecting the obligation to study on campus in the academic world. Therefore, the aim of this article is to understand the character formation and implementation of the Tahfidz Qur’an program at the Nurul Furqon 2 Malang Islamic Boarding School. The program that has been implemented starts every morning, namely morning prayers in congregation until the evening before bed, the first deposit activity is at 06:00 and the second deposit is at 16:00, the contribution produced lies in the time discipline and structured activities at each the day.